Navigating vaccine hesitancy: Strategies and dynamics in healthcare professional-parent communication - Marhánková, Jaroslava Hasmanová; Kotherová, Zuzana; Numerato, Dino (Human vaccines & immunotherapeutics, 2024)
Understanding the communication dynamics between vaccine-hesitant parents and healthcare professionals (HCPs) is vital for addressing parent concerns and promoting informed decision-making. This paper focuses on strategies used by HCPs to communicate with vaccine-hesitant parents. It draws on empirical evidence generated as part of the international project VAX-TRUST. More specifically, 60 hours of observations were carried out in three different pediatric practices during vaccination-related visits, and 19 physicians and nurses were interviewed. We focused on the specific context of the Czech Republic, which represents a country with a mandatory vaccination system and in which children's immunization is the responsibility of pediatric general practitioners. We demonstrate that the dynamics between parents and HCPs and their willingness to invest time in the vaccination discussion are influenced by how HCPs categorize and label parents. Furthermore, we outline some of the different strategies HCPs employ while addressing concerns regarding vaccination. We identified two different strategies HCPs use to manage the fears of vaccine-hesitant parents. The first strategy focused on the communication of risks associated with vaccination (and lack thereof). HCPs used a variety of discursive practices to familiarize the unfamiliar risks of vaccine-preventable diseases (by mobilizing representations that are part of collective memory, incorporating personal experiences to materialize the presence of risk and the confidence in the safety of vaccines and by situating risk as embedded in everyday processes and integral to the uncertainty of the global world). The second strategy involved the conscious employment of medical procedures that may contribute to reducing vaccination fears.
Keywords: rodiče; Male; Health Personnel; Female; zdravotnický personál; dítě; vztahy mezi odborníkem a rodinou; komunikace; Communication; Česká republika; Vaccination; rozhodování; Health Knowledge, Attitudes, Practice; mužské pohlaví; vakcíny; ženské pohlaví; Decision Making; Adult; Czech Republic; Child; Parents; vakcinace; dospělí; pacientův souhlas se zdravotní péčí; Vaccines; Professional-Family Relations; Vaccination Hesitancy; lidé; odkládání očkování; Humans; zdraví - znalosti, postoje, praxe; Patient Acceptance of Health Care